DEVELOPMENT OF INTERACTIVE DIGITAL PICTURE STORY MEDIA TO ENHANCE FIFTH-GRADE STUDENTS' READING LITERACY IN MENGWI DISTRICT - Ni Kadek Ayu Dewi Sukartini; Ni Ketut Diah Damayanti; Ni Nyoman Kurnia Wati (SOSIOEDUKASI, 2026)
This research aimed to develop an interactive digital picture story-based learning media that is valid, practical, and effective in enhancing reading literacy among fifth-grade elementary students in Cluster 2 of Mengwi District. Using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), the study involved 28 fifth-grade students and one classroom teacher at SD Negeri 2 Mengwi. Data were collected through expert validation sheets assessing content, language, and visual design; teacher and student practicality questionnaires; and reading literacy tests (pretest–posttest). Validity testing yielded an overall score of 88.6%, categorized as "very valid." Practicality assessment showed an average score of 88.7%, indicating high usability and acceptance by both teachers and students. Effectiveness testing revealed a statistically significant improvement in reading literacy scores, increasing from 65.21 (pretest) to 82.43 (posttest) with p = 0.000 (< 0.05). Normalized gain (N-gain) reached 0.49 (medium category), confirming meaningful enhancement in students' text comprehension abilities. These findings demonstrate that the developed media successfully integrates visual, textual, and interactive elements to create engaging, culturally relevant reading experiences aligned with Mayer's (2021) Multimedia Learning Theory and Vygotsky's (1978) constructivist principles. The media represents a viable innovation for Indonesian language instruction that transforms passive reading into active, meaningful literacy development.